“I have never done that before, so I will probably succeed”: higher education students' self-efficacy after the COVID-19 pandemic - Bjerke, Victoria Rustad; Olsson, Maria I. T.; Bjørnsen, Ragnhild; Myklebø, Sigrid; Tveita, Thale Charlotte (Frontiers in Education, 2025)
IntroductionThe COVID-19 pandemic led to the cancellation of traditional exams for Norwegian upper secondary schools, resulting in the “COVID-19 cohort” graduating with little or no exam experience. This study explores how this impacted their self-efficacy upon entering higher education. Guided by Bandura's social cognitive theory, it identifies mastery experiences, modeling behaviors, verbal persuasion, and physiological states as key predictors.MethodsTo explore this, we conducted a survey among first- to third-year students (n = 248) at a Norwegian university in autumn 2022.ResultsStudents emphasized "prior experiences" and "teacher feedback" as vital for self-efficacy, though many reported receiving limited feedback. Interestingly, despite lacking exam experience-a central predictor of self-efficacy-students largely felt unaffected by this.DiscussionThe pandemic's impact may not necessitate significant curriculum adjustments in higher education. However, some students believed easier coursework would enhance self-efficacy, a view inconsistent with self-efficacy theory, which underscores the value of challenging, resilience-building experiences.